Novel computed tomography-based tools reliably quantify plant reproductive investment. (23rd December 2017) - Staedler, Y M; Kreisberger, T; Manafzadeh, S; Chartier, M; Handschuh, S; Pamperl, S; Sontag, S; Paun, O; Schönenberger, J
Abstract : New computed tomography-based tools allow plant reproductive investment to be quantified, and their use is demonstrated by studying the differences in pollen/ovule ratios across inflorescences of deceptive versus rewarding orchid species. Abstract: The flower is a bisexual reproductive unit where both genders compete for resources. Counting pollen and ovules in flowers is essential to understand how much is invested in each gender. Classical methods to count very numerous pollen grains and ovules are inefficient when pollen grains are tightly aggregated, and when fertilization rates of ovules are unknown. In this study we have therefore developed novel counting techniques based on computed tomography. In order to demonstrate the potential of our methods in very difficult cases, we counted pollen and ovules across inflorescences of deceptive and rewarding species of European orchids, which possess both very large numbers of pollen grains (tightly aggregated) and ovules. Pollen counts did not significantly vary across inflorescences and pollination strategies, whereas deceptive flowers had significantly more ovules than rewarding flowers. The within-inflorescence variance of pollen-to-ovule ratios in rewarding flowers was four times higher than in deceptive flowers, possibly demonstrating differences in the constraints acting on both pollination strategies. We demonstrate the inaccuracies and limitations of previously established methods, and the broad applicability of our new techniques: they allow measurement of reproductive investment without restriction on object number or aggregation, and without specimen destruction.